PARTICIPACIÓN DE LOS PADRES DE FAMILIA EN EL PROCESO EDUCATIVO DE LA INSERCIÓN SOCIAL DE L OS NIÑOS/AS DE LA INSTITUCION ESPECIALIZADA PARA CIEGOS BYRON EGUIGUREN, Y LA INTERVENCIÓN DEL TRABAJO SOCIAL. - Orellana Pardo, Giselle Elizabeth (2015)
The parents’ involvement in the educational process is essential to every child throughout their training, and even more when we are dealing with children with some type of visual impairment; with regard to this situation the investigation based on the study of the following research problem: "THE PARENTS’ LOW LEVEL OF PARTICIPATION IN THE EDUCATIONAL PROCESS OF CHILDREN’S SOCIAL INTEGRATION OF " SPECIALIZED FOR BLIND BYRON EGUIGUREN INSTITUTION”; this same process is aimed to contribute to the strengthening of active and responsible parents in the educational process of social inclusion of children participation. For the development of this research we applied the method for the community itself, which, through the initial exchange with the subject in need of professional action, involves the empirical exploration stage data that captures the subject under investigation was applied; diagnosing and finding solutions to this problem. For the collection of accurate data enabling comply with the Specific Objectives: Base theoretical and methodological conceptions related to the parents’ participation in the education process of social integration of their children; specifying the causes and effects that generate it; 18 students and 16 of the students’ parents were surveyed at the same, just as we used information from social files and the students’ relatives were collected and made use of cell phone calls aimed at parents who live outside the city of Loja. That is why this research aims to raise the parents’ level of participation in the education process of social integration of children, from the Social Work point of view, through a proposal to raise awareness about the damage due to their lack of involvement and detachment, thus fulfilling the third goal set.